2003
DOI: 10.1128/aac.47.6.2056-2058.2003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CMY-2, CTX-M-14, and SHV-12 β-Lactamases in Escherichia coli Fecal-Sample Isolates from Healthy Chickens

Abstract: Genes encoding the CMY-2, CTX-M-14, and SHV-12 β-lactamases were detected in three of five Escherichia coli isolates from fecal samples from healthy chickens which showed resistance or diminished susceptibility to extended-spectrum cephalosporins. A −42 mutation at the promoter region of the ampC gene was detected in the other two isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(123 citation statements)
references
References 26 publications
3
114
2
1
Order By: Relevance
“…This observation is in good agreement with the previous publication of Bradford et al (10) reporting the location of genes encoding CTX-M-5 on small non-self-transferable plasmids. It may also explain the relatively low proportion of CTX-M-5-producing isolates compared to those bearing CTX-M-3 and Neither CTX-M-8-nor CTX-M-9-related enzymes were found in this study, although in recent years ESBLs of the latter genetic group were found in other European countries (Spain [9,11,35], France [18,36], and the United Kingdom [Alobwede et al, letter]) as well as in Asian countries (Japan [41], China [14], Taiwan [22,44], Korea [28], and Vietnam [13]) and Brazil (8).…”
Section: Resultscontrasting
confidence: 44%
“…This observation is in good agreement with the previous publication of Bradford et al (10) reporting the location of genes encoding CTX-M-5 on small non-self-transferable plasmids. It may also explain the relatively low proportion of CTX-M-5-producing isolates compared to those bearing CTX-M-3 and Neither CTX-M-8-nor CTX-M-9-related enzymes were found in this study, although in recent years ESBLs of the latter genetic group were found in other European countries (Spain [9,11,35], France [18,36], and the United Kingdom [Alobwede et al, letter]) as well as in Asian countries (Japan [41], China [14], Taiwan [22,44], Korea [28], and Vietnam [13]) and Brazil (8).…”
Section: Resultscontrasting
confidence: 44%
“…β-lactamase and ESBL's have also been detected in E. coli isolates from healthy chickens, food and sick animals in Spain (Brinas et al, 2003a;Brinas et al, 2003b;Brinas et al, 2002). The use of extended-spectrum cephalosporins in chickens is very unusual, and the possibility of cross-selection with other antimicrobials used in poultry (such as sulphonamides and tetracyclines, among others) might explain this discovery.…”
Section: E Coli Strains Producing An Extended Spectrum β-Lactamase (mentioning
confidence: 95%
“…The first ESBL-producing E. coli (CTX-M-14, SHV-12, and CMY-2) in poultry were isolated from healthy chick feces in Spain in 2000 and 2001 (7). Recently published literature reported that the most common ESBL-type E. coli in healthy poultry were CTX-M-1 in France (12) CTX-M-65) and TEM in China (14).…”
Section: Discussionmentioning
confidence: 99%
“…Randomly choosing a colony from each cloacal sample, bla CTX-M (CTX-M groups 1, 8, 9, and 10), bla TEM, bla OXA-1, bla FOX, bla CMY, bla SHV , and ampC beta lactamase genes were studied using PCR (7,8). All obtained amplicons were sequenced on both strands, and sequences were compared with those included in the GenBank database and on the website http:/www.lahey.org/Studies/ to identify the betalactamase genes.…”
Section: Characterization Of Esbl Genesmentioning
confidence: 99%